(untitled) (Journal of University of Babylon for Engineering Sciences, 2019)
A comprehensive review on wide range of studies on natural convection was published relevant to enclosures especially for the nanofluid enclosures which were exposed to different conditions on its boundary wall. The papers related to the ways that used to enhancement the natural convection heat transfer of a nanofluid within an enclosure region had been discussed in full details. Also contains the experimental and numerical studies related to natural convection heat transfer of a nanofluid. It is of practical and scientific importance to several engineering applications, such as industrial cold-storage installations and insulation for buildings. There are researchers attracted their attention and interested in studying the thermophysical characteristics of the nanoparticle more than anything else of the studies and did not focus on the characteristics of heat transfer by this new fluid. There was a series of investigations and several experimental and numerical studies were investigating within a square shape cavity using nanofluids as working fluid and with the effect of the conductive baffle has a variable-length attached to the bottom horizontal wall. It was found that there is a lot of things need to be investigated for studying the nanoparticle size and shape influence on the natural convection heat transfer inside an enclosure.